2017
DOI: 10.1021/acs.biochem.7b00060
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of AP Lyase and m6A Demethylase Activities of Human AlkB Homologue 1 (ALKBH1)

Abstract: Alkbh1 is one of nine mammalian homologs of Escherichia coli AlkB, a 2-oxoglutarate-dependent dioxygenase that catalyzes direct DNA repair by removing alkyl lesions from DNA. Six distinct enzymatic activities have been reported for Alkbh1, including hydroxylation of variously methylated DNA, mRNA, tRNA, or histone substrates along with the cleavage of DNA at apurinic/apyrimidinic (AP) sites followed by covalent attachment to the 5′-product. The studies described here extend the biochemical characterization for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 73 publications
2
18
0
Order By: Relevance
“…We previously showed that His-tagged ALKBH1 Ec possessed low m 6 A demethylase activity using ssDNA and cleaved 3′ of abasic sites in ssDNA and double-stranded (ds) DNA via β-elimination [1315]. Here, we tested whether ALKBH1 293 also exhibits these activities.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…We previously showed that His-tagged ALKBH1 Ec possessed low m 6 A demethylase activity using ssDNA and cleaved 3′ of abasic sites in ssDNA and double-stranded (ds) DNA via β-elimination [1315]. Here, we tested whether ALKBH1 293 also exhibits these activities.…”
Section: Resultsmentioning
confidence: 96%
“…Unusual for an AP lyase, ALKBH1 Ec is a single-turnover enzyme that forms an adduct with the α,β-unsaturated aldehyde 5′ product of the β-elimination reaction [14, 15, 20]. We tested whether ALKBH1 293 catalyzes the same covalent attachment reaction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies also showed that the proteins of the AlkB family, such as NMAD-1 in C. elegans (23), DMAD in D. melanogaster (24), and ALKBH1 in mouse and human (27,35), can regulate m 6 dA level in genomic DNA. The in-vitro assay showed that ALKBH1 can induce the decline of m 6 dA in DNA (36,37). Along this line, we hypothesize that N 6 -hydroxymethyl-2′-deoxyadenosine (hm 6 dA) can be formed from the hydroxylation of m 6 dA by ALKBH1 in genomic DNA of mammals (Figure 1).…”
Section: Introductionmentioning
confidence: 99%